2004
DOI: 10.1161/01.cir.0000129502.10459.fe
|View full text |Cite
|
Sign up to set email alerts
|

Statins as Immunomodulatory Agents

Abstract: Abstract-Statins have long been thought to exert their benefits by reducing cholesterol synthesis. However, the fact that mevalonate is the precursor of isoprenoids that regulate diverse cellular functions has led investigators to examine pleiotropic effects for these agents. Major histocompatibility complex class II (MHC-II) molecules, which affect the immune response and organ rejection after transplantation, may be induced by the proinflammatory cytokine interferon gamma (IFN-␥). An experiment was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 26 publications
2
59
0
1
Order By: Relevance
“…This effect was dose dependent and was abrogated when statins were administered together with 200 μM mevalonate, a metabolite that reverses statin-mediated inhibition of the cholesterol synthesis pathway ( Figures 3A and 4A ). 27 Similar results were observed with another member of the statin class of drugs, atorvastatin (see supplementary Figures 1A and 2A online at www.ajtmh.org ).…”
Section: Resultssupporting
confidence: 81%
“…This effect was dose dependent and was abrogated when statins were administered together with 200 μM mevalonate, a metabolite that reverses statin-mediated inhibition of the cholesterol synthesis pathway ( Figures 3A and 4A ). 27 Similar results were observed with another member of the statin class of drugs, atorvastatin (see supplementary Figures 1A and 2A online at www.ajtmh.org ).…”
Section: Resultssupporting
confidence: 81%
“…Laboratory investigations have shown that cessation of statin therapy results in rapid worsening of inflammatory parameters such as C‐reactive protein10, 11, 12 as well as endothelial function 13, 14. Exposure to statins in the acute phase of experimental stroke appears to promote angiogenesis and synaptogenesis,15 and additional pleiotropic statin effects such as vasodilatory and antithrombotic properties have been reported 16. These experimental observations are supported by clinical findings of improved outcomes with acute statin use in myocardial infarction,17, 18, 19 stroke,3, 4, 20, 21 and major vascular surgery 22, 23…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their cholesterol-lowering effect, recent reports suggest that statins also possess antiinflammatory and immunomodulatory actions. 37,38 Nevertheless, several adverse events have been reported, such as renal toxicity and rhabdomyolysis, in patients treated with statins. 39,40 Although the precise reason for these effects is not fully understood, it appears that they are in part the result of mitochondrial toxicity and selenoprotein deficiency.…”
Section: Fougerat Et Al Phosphoinositide 3-kinase-␥: Key To Atherosclmentioning
confidence: 99%